Synthesis of β-hydroxyacetamides from unactivated ethyl acetates under base-free conditions and microwave irradiation. Issue 1 (15th January 2015) - Hernández-Fernández, Eugenio; Sánchez-Lara, Pedro Pablo; Ordóñez, Mario; Ramírez-Marroquín, Oscar Abelardo; Avalos-Alanís, Francisco G.; López-Cortina, Susana; Jiménez-Pérez, Víctor M.; Ibarra-Rivera, Tannya Rocio
Graphical abstract